Studies on anti-hypercholesterolemic activity of Indanyl tetrazoles - Adak, M (Journal of Institute of Medicine Nepal, 2011)
Introduction: Clinically useful non-steroidal antihyperlipidemic drugs are now in the market for the treatment of patients suffering from hypercholesterolemia. Indan acids, which belong to non-steroidal aryl alkanoic acids class acids have been reported to possess varying degrees of cholesterol lowering activity. Keeping the above points in view exploration for better anti-hypercholesterolemic activity of indanyl tetrazole derivatives was undertaken. Methods: Five-week-old male albino Charles Foster rats (120± 10 g) for normocholesterolemic and seven-week-old rats (130±10g) for hypercholesterolemic studies were used. On the 0-day and 14th day, tail vein blood was drawn from the overnight fasted animals respectively. Biochemical measurements were carried out using biochemical kits (Span, India) and an automated biochemical analyzer (Vitros-250, Johnson and Johnson Co. USA). Results: The compound - V and VI exhibited almost same significant level of cholesterol lowering (p